A comparative study between first three waves of COVID-19 pandemic with respect to risk factors, initial clinic-demographic profile, severity and outcome - Indranil Thakur; Arabinda Chatterjee; Ashis Kumar Ghosh; Shiv Sekhar Chatterjee; Santanu Saha; Tanmaykanti Panja; Utpal Dan (Journal of Family Medicine and Primary Care, 2024)
Introduction: During the 2 years and 9 months from March 2020 to December 2022, the SARS-CoV-2 virus raged across the country. Cases occurred in three particular time clusters recognised by World Health Organisation as coronavirus disease 2019 (COVID-19) waves. In this study, we compare the clinical parameters of adult non-obstetric COVID-19 patients admitted to our rural tertiary care hospital during the three distinct waves of the pandemic. Materials and Methods: Retrospective chart analysis of 272, 853 and 97 patients admitted with SARS-CoV-2 infection to the only rural medical tertiary care centre in the Sunderbans of West Bengal in the first, second and third waves, respectively, was done after obtaining ethical and scientific clearance. Clinical [vital parameters, oxygen requirement, mental status, risk factor assessment, duration of hospital stay, modified-emergency warning score (m-EWS), quick Sequential Organ Failure Assessment (qSOFA), confusion, uraemia, respiratory rate, blood pressure, age ≥ 65 years (CURB65)], epidemiological variables (age, gender, and vaccination status), laboratory parameters and in-hospital outcome were recorded and analysed statistically. Results: Statistically significant (P < 0.05) m-EWS and qSOFA scores were recorded during the second wave of the pandemic. The second wave also recorded the highest mortality (14.89%) compared to the first (12.87%) and third (11.96%) waves, though this was not statistically significant. The highest duration of hospital stay was recorded in the first wave of the pandemic (mean = 9.99 days, P < 0.01). The difference in mortality rates between patients with and without co-morbidity (P < 0.05) was observed during Wave-1, across any pandemic wave, and overall but not in Wave-2 and Wave-3. Conclusion: The second wave of the COVID-19 pandemic was the most severe in comparison with the other two waves, while the outcome was poorer in those with co-morbidities, especially in the first wave.